Transdisciplinarity in strategic decisions for oncological treatments - Fernandes, I.; Rueff, M. C.; Portela, S. (Medicine and Law, 2015)
The current models for equity and access to new oncological treatments are under strain due to the economic and demographic crisis in Europe as well as the rising costs of innovative drugs. Cancer treatment needs a model of patient-centered care in which an interdisciplinary care plan, based on evidence-based practice is essential for patient wellbeing. Physicians should be focused in the doctor-patient relationship and informed consent is important, especially when new medicines are prescribed. Related with informed consent, there is therapeutic privilege. Moreover, utilitarianism and social justice have to be considered without compromising human dignity and the principle of economy cannot be ignored in the provision of public services. An interdisciplinary approach is essential for the new oncological drugs approval. Therefore, transdisciplinary decision between civil society, pharmaceuticals, healthcare professionals and policy makers is essential in order to assure quality, access to innovation and equity in oncological care.